Discovery and optimisation of potent and highly subtype selective Nav1.8 inhibitors with reduced cardiovascular liabilities12. Issue 10 (29th July 2016) - Bagal, Sharan K.; Kemp, Mark I.; Bungay, Peter J.; Hay, Tanya L.; Murata, Yoshihisa; Payne, C. Elizabeth; Stevens, Edward B.; Brown, Alan; Blakemore, David C.; Corbett, Matthew S.; Miller, Duncan C.; Omoto, Kiyoyuki; et al.
Abstract : Potent and subtype selective Nav 1.8 inhibitors were designed and optimised for selectivity over hERG ion channel inhibition. Abstract : Voltage-gated sodium channels, in particular Nav 1.8, can be targeted for the treatment of neuropathic and inflammatory pain. Herein, we describe the discovery and optimisation of a Nav 1.8 inhibiting phenyl imidazole series that delivers chemical equity that possesses high potency and selectivity and is capable of demonstrating good oral pharmacokinetics.